Assessing and evaluating the feasibility of 3D printed aluminium alloys from industrial scraps - Chng, Samuel Xian Mao (Nanyang Technological University, 2024)
Aluminium is the second most produced metal in industry today and its production volume is only predicted to increase. However, the production of primary aluminium is extremely energy consuming and responsible for large amounts of emissions that are detrimental to the environment. The aluminium is then machined to produce the final product, resulting in almost half of the material being scrapped along the manufacturing chain. As a result, recycling of aluminium has become a topic of interest in recent times. The conventional method of recycling aluminium results in only half the material being recoverable. As a result, research into a more productive method of recycling aluminium is popular recently. Some research has been done into turning aluminium scraps into powder for metal injection moulding or powder metallurgy, but little has been done to assess the suitability of 3D printing as a mean of recycling such scraps. This undertaking attempts to comminute aluminium scraps using mechanical processes like ball mill, centrifugal mill and cutting mill. The powders obtained were then analysed, and analysis of single track fabrication was conducted. Ideal hatch spacing to reduce build time without sacrificing on the quality of fabricated products was calculated based on the cross-sectional profile of the melt pool. A normalised processing diagram which highlights selections of process parameters that are more probable to result in an SLM-fabricated sample with low porosity was also presented. The paper proposes possible methods to successfully comminute aluminium scraps into SLM powder and suggests process parameters for further research.